Development of AODV based static multi-hop linear routing algorithm using 802.11 wireless sensor network for oil and gas pipeline - Mohamad Yusry Lee, Ikhwan Lee (2022)
In recent years, the growing requirement for a static multi-hop wireless sensor network (WSN) has dominated remote supervision of the integrity of oil and gas pipelines. In the pipeline network, the sensing points are linked via wireless nodes connecting inspection points remotely to a centralised monitoring station. The introduction of the WSN to the pipeline network has critical factors leading to the deterioration of the overall network performance corresponding to the density of the network. In the selected application, the midstream of the oil and gas industry, the nodes must be arranged in a linear architecture to cover the length of the pipe. Such geographically diverse network configuration has a major effect on the disintegration of network stability, throughput unfairness, higher latency and energy usage from improper exploitation of network resources due to competitive data transmission, resulting in data snowballing effect on the destination node. Node starvation is also a factor that seriously affects the network performance of a large scale WSN multi- hop linear network. Unbalanced allocation of network resources between source nodes leads to the starvation of the node, which is a comparatively intensified factor overproduced data packets and source node distance from the destination node. Energy improvement in a static multi-hop linear topology is also linked to the lifetime of the network and is essential to the heterogeneous energy consumption nodes in the network. To decipher the mentioned problems, this thesis highlighted the challenges faced during the deployment of WSN in a large-scale network. The objective of this research is to develop a reliable AODV based multi-hop linear routing algorithm in accordance with IEEE 802.11 and to analyse the network performance implementing the proposed technique. This thesis highlighted two proposed routing algorithms namely Ad-hoc On-Demand Distance Vector Even, and Odd (AODVEO) and Ad-hoc On-Demand Distance Vector Triple Interleaving (AODVTRI) benched marked with commercial routing protocols Ad-hoc On-Demand Distance Vector (AODV) as well as Distance Sequence Distance Vector (DSDV). In AODVEO, the load of the traffic is reduced by splitting the traffic into two different routes (1) even-path and (2) odd-path with the consideration of x-axis. On the other hand, in AODVTRI, the traffic is divided into three different routes (1) alpha path, (2) beta path, and (3) charlie path with consideration of x-axis. Results showed that when the proposed technique is compared to the existing routing protocols in different simulation environments in conjunction with IEEE 802.11 standard, AODVEO showed improved network reliability (delivery ratio) as high as 19% and 15% in comparison to AODV and DSDV. In contrast, AODVTRI presented up to 26% and 22% of improvement when compared to AODV and DSDV, respectively. In terms of capacity (throughput) as well as energy, AODVEO showed up to 9 kbps more with 0.038J less energy consumption per packet and up to 13kbps more with 0.095J less energy consumption per packet when compared to AODV and DSDV. AODVTRI, on the other hand, showed up to 18 kbps more throughput with 0.082J less energy per packet when compared to AODV and up to 22kbps more with 0.140J less energy consumption per packet when compared to DSDV.